WW-Domain Containing Protein Roles in Breast Tumorigenesis - Jamous, Abrar; Salah, Zaidoun (Frontiers in Oncology, 2018)
Protein-protein interactions are key factors in executing protein function. These interactions are mediated through different protein domains or modules. An important domain that is found in many and different types of proteins is WW domain. WW domain-containing proteins were shown to be involved in many human diseases including cancer. Some of these proteins were shown to function as either tumor suppressor genes or oncogenes, while others were shown to have dual identity. While some of these proteins act on their own and alter the function of a specific or multiple proteins implicated in cancer, some of these proteins interact with their partners to compose WW domain modular pathway. In this review, we discuss the role of WW domain-containing proteins in breast tumorigenesis. We will give examples of specific WW domain containing proteins that play roles in breast tumorigenesis and explain the mechanisms through which these proteins lead to breast cancer initiation and progression. We will discuss also the possibility of using these proteins as biomarkers or therapeutic targets.